2021
DOI: 10.1111/aswp.12227
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress and trauma during the COVID‐19 pandemic: Evidence from Bangladesh

Abstract: The COVID‐19 outbreak has become a global health crisis affecting both the physical and mental health of people across the world. Likewise, the people of Bangladesh are going through a menacing mental health catastrophe with the outbreak of coronavirus that resulting in stress and trauma. Hence, this situation is altering people's lifestyles and generating complexities in psychological well‐being. The study was based on the review of published articles and media reports related to stress and trauma during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Nyashanu et al 22 argued that the shortage of PPEs, insufficiencies in COVID-19 preparedness, and lack of scope for maintaining social distancing were among the reasons for the stress and fear affecting healthcare personnel, in addition to the health catastrophe itself. According to Hossain et al 6 healthcare providers were stressed and traumatized due to a lack of required safety equipment, fear of infection, and lack of COVID-19 management coordination. Such stress, mental trauma, lack of needed resources, and management failures led to a decline in work competence among these professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nyashanu et al 22 argued that the shortage of PPEs, insufficiencies in COVID-19 preparedness, and lack of scope for maintaining social distancing were among the reasons for the stress and fear affecting healthcare personnel, in addition to the health catastrophe itself. According to Hossain et al 6 healthcare providers were stressed and traumatized due to a lack of required safety equipment, fear of infection, and lack of COVID-19 management coordination. Such stress, mental trauma, lack of needed resources, and management failures led to a decline in work competence among these professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 health hazard has had a devastating effect on Bangladesh, causing harm to people’s health and well-being. 6 People of all classes and professions are being seriously afflicted by the disaster’s waves. People who work in the medical health service have to deal with a lot of problems both at work and at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence of pandemic was more pronounced in the least developed countries, with large number of people experiencing starvation (J‐PAL, 2020 ). The World Economic Forum (WEF) reported that financial crisis during COVID‐19 pandemic was more severe than that of 2008 Global Financial Crisis (GFC) (Hossain et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the pandemic, almost every country enforced a lockdown (a state of isolation or restricted movement) to limit the spread of the contagious coronavirus (Tang et al, 2020).The outbreak does not only generate serious health problem among the people but also induce economic downturn globally (Tang et al, 2020).The consequence of pandemic was more pronounced in the least developed countries, with large number of people experiencing starvation (J-PAL, 2020). The World Economic Forum (WEF) reported that financial crisis during COVID-19 pandemic was more severe than that of 2008 Global Financial Crisis (GFC) (Hossain et al, 2021).Universal Declaration of Human Rights (UDHR) of the United Nations affirms basic human rights to social protection. Also, the International Labor Organization (ILO) (2011) actively supports policies that promote human rights and provides assistance to countries to facilitate sufficient levels of social protection to all members of society (Bachelet & Office, 2012).…”
mentioning
confidence: 99%